Cellular mechanisms of reverse epithelial curvature in tissue morphogenesis - Wang, Yiran; Stonehouse-Smith, Daniel; Cobourne, Martyn T.; Green, Jeremy B. A.; Seppala, Maisa (Frontiers in Cell and Developmental Biology, 2022)
Epithelial bending plays an essential role during the multiple stages of organogenesis and can be classified into two types: invagination and evagination. The early stages of invaginating and evaginating organs are often depicted as simple concave and convex curves respectively, but in fact majority of the epithelial organs develop through a more complex pattern of curvature: concave flanked by convex and vice versa respectively. At the cellular level, this is far from a geometrical truism: locally cells must passively adapt to, or actively create such an epithelial structure that is typically composed of opposite and connected folds that form at least one s-shaped curve that we here, based on its appearance, term as “reverse curves”. In recent years, invagination and evagination have been studied in increasing cellular detail. A diversity of mechanisms, including apical/basal constriction, vertical telescoping and extrinsic factors, all orchestrate epithelial bending to give different organs their final shape. However, how cells behave collectively to generate reverse curves remains less well-known. Here we review experimental models that characteristically form reverse curves during organogenesis. These include the circumvallate papillae in the tongue, crypt–villus structure in the intestine, and early tooth germ and describe how, in each case, reverse curves form to connect an invaginated or evaginated placode or opposite epithelial folds. Furthermore, by referring to the multicellular system that occur in the invagination and evagination, we attempt to provide a summary of mechanisms thought to be involved in reverse curvature consisting of apical/basal constriction, and extrinsic factors. Finally, we describe the emerging techniques in the current investigations, such as organoid culture, computational modelling and live imaging technologies that have been utilized to improve our understanding of the cellular mechanisms in early tissue morphogenesis.